Pós-colonialidade, pós-escravismo, bioficção e con(tra)temporaneidade - Denise Carrascosa (Estudos de Literatura Brasileira Contemporânea)
This critical essay promotes a connection between the contemporary concept from the literary theory field named “biofiction”, the post-colonial theory and the issue of Africa n - diasporic subjetivization, from the Brazilian historical experience and intellectual possibility of speech, crisscrossed with a symptomatic study of the last novels written by Toni Morrison, Home (2012), and Jamaica Kincaid, See now then ( 2013), as well as of the novel A question of power (1970) by Bessie Head. The concept of biofiction is problematized as a zone of forces related to the historical processes of subalternization linked to colonization, slavery and their reverberations, in its potential of discursive divergence and “co(unter)temporary” production of subjectivities.